2001
DOI: 10.1259/bjr.74.878.740157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of decreasing mAs on image quality and patient dose in sinus CT

Abstract: The aim of this study was to determine the effect of reducing mAs on the diagnostic quality of images and the radiation dose to the orbits in patients undergoing sinus CT. We studied 40 consecutive patients undergoing paranasal sinus CT for inflammatory disease prior to functional endoscopic sinus surgery (FESS). Four groups of 10 patients were scanned at 200 mAs, 150 mAs, 100 mAs and 50 mAs, respectively. Orbital radiation dose was measured using thermoluminescent dosemeters. Images were reviewed independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 9 publications
5
39
0
4
Order By: Relevance
“…However, a reduction of radiation dose will increase image noise, which may compromise image quality to a variable extent. 2,12,17,19,21,22 Previous studies on CT of the head and neck, chest, abdomen, and pediatric pelvis have suggested the possibility of reducing tube currents without jeopardizing imaging quality, 17,19,[23][24][25][26][27][28] but the tube current in those studies was adjusted manually. Such manual adjustment of tube current, based on patient weight or dimensions, can aid in establishing an appropriate balance between image noise and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, a reduction of radiation dose will increase image noise, which may compromise image quality to a variable extent. 2,12,17,19,21,22 Previous studies on CT of the head and neck, chest, abdomen, and pediatric pelvis have suggested the possibility of reducing tube currents without jeopardizing imaging quality, 17,19,[23][24][25][26][27][28] but the tube current in those studies was adjusted manually. Such manual adjustment of tube current, based on patient weight or dimensions, can aid in establishing an appropriate balance between image noise and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Greater attention has been directed toward adjusting CT parameters, most commonly through the reduction of milliampere-second (mAs) (tube current time product), to allow reduced radiation exposure while maintaining acceptable image quality. [3][4][5][6][7][8][9][10][11][12][13] Recently, high-pitch dual source multidetector CT systems have shown promise of even greater dose reduction. 14,15 Nevertheless, because of progressively decreasing signal-to-noise, a threshold for tube output is invariably reached, below which imaging becomes unacceptable.…”
mentioning
confidence: 99%
“…First, we used a dedicated low-dose protocol for sinusitis (sinusitis CT, 30 mAs) as amply described in the literature. [9][10][11] Second, we used a high-dose protocol for optimal soft-tissue delineation (140 mAs). Third, we had a dedicated protocol for CAS-CT (210 mAs).…”
mentioning
confidence: 99%